The Inhibitory Effect of the Derris scandens Extract on Cytochrome P450 2E1 (CYP2E1) -associated Aniline-4-Hydroxylase in vitro - Punjanon, Tadsanee (Thai Journal of Toxicology, 2018)
The indications of the 50% ethanolic extract of Derris scandens (Tao-Wan-Priang) are for relieving pain in lower back pain and knee osteoarthritis. It is well established that many herbs interact pharmacokinetically with drugs by modulating the activities of cytochrome P450s enzymes. The aim of this study was to investigate the effect of the D. scandens extract on the activity of cytochrome P450 2E1 (CYP2E1) -associated aniline-4- hydroxylase (A4H) in the rat hepatic microsome induced by phenobarbital under in vitro condition. Different concentrations of the D. scandens extract of 0, 100, 200, 400, 600, 800, and 1,000 mg/mL were added to the reaction mixture contained microsome, aniline hydrochloride, cofactor, and phosphate buffer and incubated at 37 °C for 20 minutes. Para- aminophenol, a product of A4H was measured by colorimetric method. The results clearly showed that the D. scandens extract significantly inhibited CYP2E1 with a dose dependent manner and the median inhibitory concentration (IC50) was 321.22 mg/mL.